Design, analysis and fabrication of rotational barbecue machine - Azlani, Adam Iskandar (2025)
Barbecue grilling is a popular outdoor cooking activity. The innovation for barbecue is began with cooking meat with fire but now meat cooked over a grill or pit using charcoal, gas or electric as the main thing to cooked food. Barbecue cooking often uses manually rotating technique to ensure foods to cook both sides. However, manually rotating foods on the grill can be unevenly cooking and time consuming. The objective of this project is to design and fabricate a semi auto barbecue machine consisting of a motor to ensure even cooking, improving cooking efficiency and reduce cooking time. The rotational barbecue machine project objectives are to design the motorized barbecue machine and fabricate the barbecue machine with a simple design that is easier to clean and using eco-friendly materials. A rotating grill system ensures consistent flavour and tenderness for various foods. Constructed from durable materials like mild steel, it withstands outdoor conditions such as corrosion and heat resistance. Portability options make it suitable for home use, catering events, and outdoor gatherings. Enhancing flavour, convenience, versatility, this barbecue machine revolutionizes outdoor cooking experiences. The functionality of the project is versatile for cooking method. It is a combination of two styles of cooking which is rotisserie and standard grill style.